A Study on the Contribution and Struggle of Women In the Freedom of India: The Role of Punjab Women in the Indian Freedom Struggle (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This article deals with the Indian Freedom Struggle andthe contribution of Indian women in this war of Independence. The article tellsus the participation of women of Punjab in the nationalist movement from1901-10, 1911-20, 1921-30, 1931-40 and 1941-47. In 1901 10, political  upheavals  in  the province of Bengal affected Punjabi women and few womenshowed their sympathy with the Bengali individuals. The decade 1911-20 was themost important decade as the Jallianwala Bagh tragedy and therefore the martiallaw of 1919 acted as a catalyst for making ladies consciousness for fightingfor the freedom of India. Then these women victims and alternative sympatheticwomen directly jumped into the Non-Cooperation movement of 1920. The decade1921-30, witnessed the direct involvement of girls of Punjab in the freedomstruggle and these women came into the contact of M. K. Gandhi. The decade1931-40 was the period of direct action and women of Punjab region did not sitback at their homes and got active in disobeying the government byfollowing the non-violent ways of Gandhi from 1930-34. The last seven yearsfrom 1941 to 47 were those when the women of Punjab province came forward andfought aboard men and suffered the same consequences as the men suffered. Theseactivist ladies were so trapped in this struggle, that they unheeded genderissues or put them aside until independence had been achieved and in the finishin 1947 after the accomplishment of independence, the women of Punjab weregiven credit to their deeds.